VD_FINDINFO Décision / 2016 / 249 vom 19. Oktober 2015 - VD Tribunal cantonal (2015)
ANNONCE D'APPEL, JUGEMENT PAR DÉFAUT, DÉCISION D'IRRECEVABILITÉ | 368 al. 1 CPP (CH), 371 al. 1 CPP (CH), 85 al. 4 CPP (CH), 91 CPP (CH)